PENGARUH MEDIA WORDWALL BERBASIS PROBLEM BASED LEARNING ( PBL ) DENGAN PENDEKATAN KOOPERATIF - KOLABORATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI FPB DAN KPK PADA SISWA KELAS IV UPTD SDI NGAPABOA - Suriandari, Reny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Wordwall media based on Problem Based Learning (PBL) with a collaborative cooperative approach on mathematics learning outcomes in the material of Greatest Common Factor (GCF) and Least Common Multiple (LCM) of fourth-grade students of UPTD SDI Ngapaboa. This study uses the Classroom Action Research (CAR) method which is implemented in three cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 27 fourth-grade students. Data collection techniques were carried out through observation, interviews, documentation, and learning outcome tests at the end of each cycle. The results showed an increase in student learning outcomes in each cycle. In cycle I, student learning completeness reached 60% because students still had difficulty understanding the concepts of GCF and LCM and were not yet accustomed to using Wordwall media. In cycle II, learning completeness increased to 75% along with increased student participation in group discussions and more optimal use of learning media. In cycle III, learning completeness reached 86% with increased student activity, cooperation, and problem-solving abilities. Thus, the use of PBL-based wordwall media with a collaborative cooperative approach has proven effective in improving elementary school students' mathematics learning outcomes.